Hepatic venous pressure gradient in patients with (compensated and decompensated) advanced chronic liver disease – A comparison of metabolic dysfunction-associated steatotic liver disease with alcohol-associated liver disease: A retrospective view - Lubomir Skladany; Daniela Žilinčanová; Michal Žilinčan; Stanislav Okapec; Filip Danček; Svetlana Adamcová-Selčanová; Michal Kukla; Tomáš Koller (PLoS ONE, 2025)
Background and aims Hepatic venous pressure gradient (HVPG) is a strong surrogate of severity and outcome but its relative prognostic value in metabolic dysfunction-associated steatotic liver disease (MASLD) and alcohol-associated liver disease (ALD) is yet to be clarified. We compared HVPG in MASLD with ALD and other etiologies according to cirrhosis complications. Patients and methods In our cirrhosis registry RH7, we identified patients with data on HVPG and scrutinized them against the etiology of advanced chronic liver disease (ACLD) (MASLD, ALD, Other) and specific complications of ACLD such as variceal bleeding or ascites. We excluded patients with advanced malignancies and less than 6 months of follow-up. Results We enrolled 220 patients with ALD, MASLD, and Other etiology in 128, 52, and 40 cases, respectively; te median age was 57, 60, and 52 years (P = 0.09); the proportion of females was 31, 67, and 55%, respectively (P < 0.01). Median MELD scores in ALD, MASLD, and Other etiologies were 16.0, 13.0, and 12.0 (P < 0.01), and the median HVPG was 18.0, 14.0, and 11.5 mmHg (P < 0.001). In 19, 30, and 25 compensated patients, the median HVPG was 10.0, 11.5, and 11.0 mmHg (P = 0.97). In 109, 22, and 15 decompensated patients, the median HVPG was 19.0, 15.5 and 14 mmHg (P = 0.01 for trend, difference ALD vs. other P < 0.01, ALD vs. MASLD, P = 0.295). Between decompensated MASLD and ALD patients, we observed no differences in the proportion of clinically significant portal hypertension (CSPH) (>10 mmHg). Conclusion In our cirrhosis registry study of hospitalized patients with ACLD, baseline HVPG measured for accepted indications differed according to the etiology of dACLD: patients with ALD had the highest values followed by MASLD and Other etiologies. Importantly, when looked at from the point of view of complications, the treshold for clinically significant portal hypertension remained fixed at the level recommended by BAVENO Consensus - 10 mm Hg irrespective of etiology.